HARUN NASUTION'S THOUGHTS ON ISLAMIC EDUCATION AND IMPLICATIONS WITH INDUSTRIAL REVOLUTION 5.0 - Sayed Muhammad Ichsan; Maragustam Siregar (Jurnal Recoms, 2024)
Islamic education is a solution to the various problems that plague humanity today, but in its journey Islamic education is seen as just a label, namely Islamic education is unable to reflect the practice of Islamic teachings in the field of education. Harun Nasution's idea is one form of assumptions that arise, that Islamic education if run correctly in bringing up students who are highly dedicated to society. The research uses a literature study approach or known as Library Research with a factual histrionic research model on figures that focuses on Harun Nasution's views on Islamic education and implications for contemporary Islamic education. The results of this study indicate that Islamic education in Harun Nasution's view is divided into two forms, namely basic and advanced. Basic education includes kindergarten, elementary school, junior high school, and high school, which focus on spiritual and moral approaches, and advanced education, namely universities, which focus on spiritual, moral and intellectual approaches. In this case, intellectual is using rationality as a means of analyzing existing problems. Keywords: Harun Nasution, Islamic Education, Contemporary